The Zambezi Basin - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
State of the Environment in the Zambezi Basin 2000 By Munyaradzi Chenje, Southern African Research and Documentation Centre GBP 23.95 Euro 40